Eksistensi Drama Korea pada Masa Pandemik Covid-19 di Indonesia (Sebuah Kajian Budaya Populer Korea) - Septadinusastra, Vina Alvinia (Media Nusantara, 2021)
The existence of Korean popular culture in Indonesia can not be doubted. One of the popular cultures of Korea that still exists in Indonesia is Korean drama. Since Korean drama first aired in 2002, Korean drama has remained the first choice program for some Indonesian viewer. This makes Korean drama more existent and popular as well as being the toughest competitor for the entertainment industry in Indonesia. The Covid-19 pandemic that hit all corners of the world did not detract from the existence of Korean dramas, even in Indonesia, in the Covid-19 pandemic there was a significant increase of new fans of Korean dramas. When the government makes a policy to conduct PSBB throughout Indonesia and all activities are carried out from home until productivity slowly begins to decrease, automatically the time will feel longer than before, so people need a diversion to kill the less of productive time. So, even though only stay at home for 24 hours every day, there are still activities that can be entertaining such as watching Korean dramas. At the time of the Covid-19 pandemic, Korean dramas did not disappear because in Korea, Korean dramas were still produced despite strict health protocols. This pandemic period seemed to be the right momentum to increase the popularity of Korean dramas throughout the world